A new strategy for environmental flow management by using the remote sensing method. (20th November 2021) - Yue, Zhenzhen; Huang, Wei; Xiong, Lihua; Wang, Zhuowei; Wang, Xuelei; Wang, Qian; Shen, Qian
Abstract: Implementing environmental flow (e-flow) is a key measure for restoring and managing river ecosystems. However, illegal competition for water resources or alterations of the natural flow regimes can result in the shortage of e-flow and degradation of river ecosystems. Monitoring and managing e-flow is increasingly critical and necessary in some regions. In this study, a monitoring method and guarantee rate evaluation system for e-flow was developed using remote sensing and hydrological data of the Jiulongjiang and Taizi rivers, China. The results indicated that the monthly e-flow varied with the water demand, ranging from 12.60 m 3 /s to 189.50 m 3 /s and 3.50 m 3 /s to 57.70 m 3 /s at Punan station, Jiulongjiang River and Tangmazhai station, Taizi River, respectively. Moreover, e-flow accounted for 24% of the average annual runoff for both rivers, which indicated that the ecological environment was in a fair or degrading state. Moreover, the guarantee rate of e-flow at Tangmazhai station is 100%, which indicates that the e-flow meets the requirements and is consistent with the results of the e-flow guarantee rate calculated by the actual measured flow. The guarantee rate of e-flow at Punan station is 0%, and exhibits a certain error with the actual measurement results; this is because a rectangular section exists between the maximum and minimum ecological water levels, which corresponds to a small change in the ecological water surface width of 0.9 m. The low-resolution remote sensing used in this study cannot capture this change, thus causing a large error in the measured result; however, this issue can be addressed by improving the remote sensing technique. The results showed that the monitoring method and guarantee rate evaluation of e-flow can be adopted for several basins, including larger scale river basins, and can improve e-flow management for mitigating the degradation of river ecosystems. Highlights: A novel e-flow management strategy was developed. The method used remote sensing and hydrological data of two rivers in China. Results prove the applicability of the system to manage e-flow in water basins. The system can be used to obtain better e-flow guarantee and ecosystem services.